De la république de la science à l’économie du savoir : 50 ans de politiques publiques de la recherche universitaire au Québec - Jean Bernatchez (Cahiers de la Recherche sur l'Education et les Savoirs)
This paper presents a reconstruction of public policies for university research in Quebec since 1960, considering their paradigms (or worldviews) and dynamics (the roles the actors play). The objective is to better understand these policies. The analysis first presents a portrait of the period 1960-1979, characterized by the paradigm of the republic of science. During this period, the evaluation of research was mainly based on peer review criteria. A transition period preceding the emergence of the paradigm of the knowledge economy marked the policy of academic research in the 1990’s. During this period, the norm was the evaluation of research based on several variables, namely scientific quality, socioeconomic relevance and organizational efficiency.